2023
DOI: 10.1088/1361-6528/ad1444
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole-loading strategy to improve antifungal activity and overcome cytotoxicity on human renal proximal tubular epithelial cells

Irem Coksu,
Yagmur Bozkurt,
Ilkgul Akmayan
et al.

Abstract: Ketoconazole (KTZ), an antifungal agent used to treat localized or systemic fungal infections by inhibiting ergosterol synthesis, exhibits restricted efficacy within eukaryotic cells owing to its elevated toxicity and limited solubility in water. This study aims to improve the biological activity and overcome cytotoxic effects in the renal system of the hydrophobic KTZ by incorporating it into poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) utilizing biomaterial nano-engineering techniques. KTZ-loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The negative zeta potential values of all NPs result from ionized carboxyl groups from acid-ended PLGA on the surface of the nanoparticles [44] and the presence of non-ionic PVA used as an emulsifier during synthesis, as reported by Arasoglu et al [45]. The PDI values less then 0.3, O-NPs (0.192 ± 0.027) and E-NPs (0.287 ± 0.022), confirm the production of monodisperse particles (figures 2(B)-(F)) and validate the homogeneity of particle sizes, which is consistent with the literature [37,46]. Following the production of nanoparticles through the double emulsion solvent evaporation method, the quantity of unencapsulated recombinant protein (rOmp25 or rEipB) was assessed from the supernatant.…”
Section: Synthesis and Characterization Of Plga Npssupporting
confidence: 91%
See 1 more Smart Citation
“…The negative zeta potential values of all NPs result from ionized carboxyl groups from acid-ended PLGA on the surface of the nanoparticles [44] and the presence of non-ionic PVA used as an emulsifier during synthesis, as reported by Arasoglu et al [45]. The PDI values less then 0.3, O-NPs (0.192 ± 0.027) and E-NPs (0.287 ± 0.022), confirm the production of monodisperse particles (figures 2(B)-(F)) and validate the homogeneity of particle sizes, which is consistent with the literature [37,46]. Following the production of nanoparticles through the double emulsion solvent evaporation method, the quantity of unencapsulated recombinant protein (rOmp25 or rEipB) was assessed from the supernatant.…”
Section: Synthesis and Characterization Of Plga Npssupporting
confidence: 91%
“…In the detailed examination of the release profile, it was observed that the initial burst release occurred during the first 6 h for both O-NPs and E-NPs, with the burst release of rEipB being partially higher. The rapid diffusion of active molecules localized near the surface of nanoparticles or directly adsorbed to the surface often leads to a burst release of these molecules [46,48]. Additionally, in the release study conducted at neutral pH, it is thought that the strong electrostatic repulsion between the negative charges of proteins with low isoelectric points and the carboxylic acid groups on the nanoparticle surface derived from PLGA facilitates the easy separation of adsorbed recombinant proteins from the surface of nanoparticles [49].…”
Section: Synthesis and Characterization Of Plga Npsmentioning
confidence: 99%
“…Because they show higher antioxidant activity than others, 9c and 9e loaded nanoparticles were synthesized. The process of synthesizing 9c or 9e-loaded PLGA NPs was carried out by employing the oil in water (o/w) single emulsion solvent evaporation technique, as described in the available literature [75]. Briefly, 6 mg of 9c or 9e was dissolved in 1 ml of DCM (Ridel de Haen) and 20 mg of PLGA was dissolved in 1 ml of DCM.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…The formulas provided in equations ( 3) and (4) were utilized to calculate the encapsulation efficiency (EE) and drug loading capacity (DL) of the NPs, correspondingly [77]. The average particle size and PDI measurements of the synthesized NPs were analyzed through dynamic light scattering (DLS) methodology utilizing the Zetasizer instrument (Zetasizer Nano ZS, Malvern, UK) operating with photon correlation spectroscopy [75]. The experiments were carried out at a temperature of 25 ± 0.1 °C, with a viscosity of 0.8872 cP and a refractive index of 1.330.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%